Transfusion and Risk of Infection in Canada: Update 2006. Issue 2 (1st April 2006) - MacDonald, Noni
Abstract : In Canada and other developed countries, many steps are taken to minimize the risk of infection from transfusion of blood or blood products (1). However, the infection risk can never be zero because these are biological products taken from living donors who are never 'germ free' (2). This is in contrast to drugs that can be manufactured de novo under sterile conditions in a laboratory. The present note provides an update on transfusion infection risks in Canada. It replaces the 2005 note (3) and may be helpful to practitioners in discussions with patients and parents for informed consent before blood or blood product administration. The changes in this note include new Canadian data on risk of adverse transfusion events (ATEs), including risk of bacterial infection. Transfusion-related acute lung injury and major allergic or anaphylactic reactions are more common than serious infections (4).